Identity and Nation in African Football Fans, Community and Clubs - Onwumechili, C.; Onwumechili, C.; Akindes, G.; Akindes, G. (Global Culture and Sport Series,, 2014)
The 2010 South African World Cup launched African football onto the global stage. This volume brings together top scholars on African football to explore a range of issues such as gender, identity, nationalism, history, cyber-fandom, the media and fan radicalization.